The Effect of Service Quality on Consumer Loyalty with Consumer Satisfaction as a Moderation Variable at Banyuwangi Kopiteko Shop - Moh. Fajar Firmansyah; Nuruni Ika Kusuma W (Indonesian Journal of Business Analytics, 2023)
The purpose of this research is to obtain some information and analyze the influence of service quality on consumer loyalty with consumer satisfaction as a moderation variable in Banyuwangi coffee shops. The population in this study is all consumers who make purchases at least twice at the Teapot Coffee Shop. The sample in this study required 91 respondents. The sample criteria needed are consumers who have made a purchase at least twice and are 17 years old and over. Sampling using purposive sampling technique. Respondent data was collected from questionnaires directly. Data analysis techniques using PLS-based SEM (Structural Equation Modeling) (Partial Least Square) with the help of smart PLS applications.  The results of this study show that Service Quality has a positive and significant effect on Consumer Loyalty at Teko Banyuwangi Coffee shop. Meanwhile, Consumer Satisfaction has a positive and insignificant influence on Consumer Loyalty of Teko Banyuwangi Coffee Shop.